Chapter Il mare, la tempesta, la quiete: un passaggio fondamentale nella trama e nel significato del Filocolo - Gigli Cervi, Isabel (Studi e saggi, 2020)
This paper inquires the characteristic elements of Filocolo, linked to sea and tempest elements, interpreted as symbolic transpositions of the love oriented sentiment. In the context of Boccaccio's youth productions, incursions in Dante's Vita Nova and Commedia are suggested too, without neglecting some reenactments of Classical sources.